TINJAUAN YURIDIS PENGANGKATAN ANAK WARGA NEGARA INDONESIA OLEH WARGA NEGARA ASING BERDASARKAN PERATURAN PEMERINTAH NOMOR 54 TAHUN 2007 TENTANG PELAKSANAAN PENGANGKATAN ANAK - Epi br Pakpahan; Hayatul Ismi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Child is one of the best God blessing so that they must have protection from their parent and the environment. Now adays there so many children don’t get protection either from the family and the environment. According to give protection to them adoption become the final decision. In adoption we must concern the best interest for children. Generally there are two kind of adoption first domestic adoption, and Intercountry adoption. Indonesia has regulation for Adoption Peraturan Pemerintah 2007 Number 54.In this writer will explain about Intercountry adoption dan try to describe however intercountry adoption give positive contribution for protection of the children right. The method that I apply in this is analisys normative which is using primer data and skunder data. The conclusion from writer about intercountry adoption is the regulation Peraturan Pemerintah 2007 Number 54 that we have is not enough to give protection for right of the children. There are still have weakness so it give opportunity to unresponsibility person to do their crime such as trafficking.So the most important thing that Indonesia must do is ratification The Den Haag Convention “Convention On Protection Of The Children and Cooperation In Respect Of Intercountry Adoption” conclude 29 May 1993. Now adays the intercountry adoption inIndonesia not yet give guarantee on protection of the Children right. Indonesia try to repairs the law so in the future intercountry adoption can give positive impact for protection of the children right which is children is weak individu as phisicly an mentally so they need our protection.Keywords: Adoption.